New Onset Diabetes Mellitus in Living Donor versus Deceased Donor Liver Transplant Recipients: Analysis of the UNOS/OPTN Database - Anitha D. Yadav; Yu-Hui Chang; Bashar A. Aqel; Thomas J. Byrne; Harini A. Chakkera; David D. Douglas; David C. Mulligan; Jorge Rakela; Hugo E. Vargas; Elizabeth J. Carey (Journal of Transplantation)
New onset diabetes after transplantation (NODAT) occurs less frequently in living donor liver transplant (LDLT) recipients than in deceased donor liver transplant (DDLT) recipients. The aim of this study was to compare the incidence and predictive factors for NODAT in LDLT versus DDLT recipients. The Organ Procurement and Transplant Network/United Network for Organ Sharing database was reviewed from 2004 to 2010, and 902 LDLT and 19,582 DDLT nondiabetic recipients were included. The overall incidence of NODAT was 12.2% at 1 year after liver transplantation. At 1, 3, and 5 years after transplant, the incidence of NODAT in LDLT recipients was 7.4, 2.1, and 2.6%, respectively, compared to 12.5, 3.4, and 1.9%, respectively, in DDLT recipients. LDLT recipients have a lower risk of NODAT compared to DDLT recipients (hazard ratio = 0.63 (0.52–0.75), P<0.001). Predictors for NODAT in LDLT recipients were hepatitis C (HCV) and treated acute cellular rejection (ACR). Risk factors in DDLT recipients were recipient male gender, recipient age, body mass index, donor age, donor diabetes, HCV, and treated ACR. LDLT recipients have a lower incidence and fewer risk factors for NODAT compared to DDLT recipients. Early identification of risk factors will assist timely clinical interventions to prevent NODAT complications.